Genome-wide identification and expression analysis of auxin response factor gene family in Medicago truncatula - Shen, Chenjia; Yue, Runqing; Sun, Tao; Zhang, Lei; Xu, Luqin; Tie, Shuanggui; Wang, Huizhong; Yang, Yanjun (Frontiers in Plant Science, 2015)
Auxin response factors (ARFs) bind specifically to auxin response elements (AuxREs) in the promoters of down-stream target genes and play roles in plant responses to diverse environmental factors. Using the latest updated Medicago truncatula reference genome sequence, a comprehensive characterization and analysis of 24 MtARF genes were performed. To uncover the basic information and functions of MtARF genes during symbiosis, we analyze the expression patterns of MtARF genes during the early phase of Sinorhizobium meliloti infection. The systematic analysis indicated that MtARF gene expressions were involved in the symbiosis processes. Furthermore, the roles of MtARF-mediated auxin signaling in symbiosis were tested in the infection resistant mutant (dmi3). The expression responses of MtARFs to S. meliloti infection were attenuated in the mutant compared to wild-type A17. In summary, our results shed that the MtARF gene expressions was involved in responses to S. meliloti infection, which may play an essential role in the regulation of nodule formation.